Market prospect of makapuno nuts in the Philippines - Elauria, Marilyn M.; Manilay, Alessandro A.; Dagaas, Clarita T.; Abrigo, Girlie Nora A. (2011)
Producing makapuno nuts from makapuno-bearing coconut trees called kanuwig provides limited and unreliable supply that barely satisfies the requirement of makapuno processors and exporters. The University of the Philippines Los Baños (UPLB) developed as technology to produce coconut that bear 75 to 100% makapuno nuts through embryo culture. The technology was improved by the Philippines coconut authority (PCA) by shortening the process of production. With financial assistance from the Philippine Council of Agriculture, Forestry and Natural Resouces Research and Development (PCARRD), PCA established embryo culture laboratories to produce and sell makapuno plantlets.

This study was conducted to determine whether the technology and the efforts of PCA and PCARRD increase the number of facilities to produce makapuno plantlets were able to ease the demand-supply gap in the makapuno industry. Demand for makapuno nuts was estimated by determining the nuts required by selected makapuno processors in the Philippines. The estimated were validated using data generated by a previous study. Supply of makapuno nuts was determined on the basis of the number of embryo-cultured makapuno plantlets that were disposed (sold or given away as gifts) by the laboratories. Forty-four years after the technology was developed, the supply of makapuno nuts has not fully met the demand of makapuno processing industry. For 2010, the slack was estimated to be 4.67 million nuts. constraints to increase production of makapuno nuts were also identified.
Keywords: Coconut industry -- Supply and demand